Energy efficiency strategy in data centers: a systematic review - Leitura, Entende; Leitura, Entende (Latin American Journal of Energy Research, 2025)
: A massive amount of data is processed daily in a Data Center (DC), and this workload has been increasing every year due to the expansion of cloud-based services and large-scale applications. In this context, a systematic review was conducted focusing on a quantitative and qualitative analysis of articles published in different parts of the world, with the objective of presenting actions and strategies developed in various contexts to address the growing energy consumption in these environments. Furthermore, challenges related to the quality and continuity of power supply are highlighted, as they directly and indirectly affect the operation of Data Centers. With each technological expansion, new investments in equipment are required, which consequently lead to higher energy demand. Finally, this study presents the selection of articles based on established criteria and their respective contributions to the adoption of best practices that promote the efficient and sustainable operation of DC.
Keywords: data center; energy efficiency; cooling system